The bright end of the colour-magnitude relation of cluster galaxies - Jiménez, Noelia (2011)
We investigate the physical processes involved in the development of the red sequence (RS) of cluster galaxies by using a combination of cosmological N-body simulations of clusters of galaxies and a semi-analytic model of galaxy formation. Results show good agreement between the general trend of the simulated RS and the observed colour-magnitude relation (CMR) of early-type galaxies in different magnitude planes. However, in many clusters, the most luminous galaxies (MR ∼ MV ∼ MT1 ≲ −20) depart from the linear fit to observed data, as traced by less luminous ones, displaying almost constant colours. With the aim of understanding this particular behaviour of galaxies in the bright end of the RS, we analyse the dependence with redshift of the fraction of stellar mass contributed to each galaxy by different processes, i.e. quiescent star formation, and starbursts triggered by disc instability and merger events. We find that the evolution of galaxies in the bright end since z ≈ 2 is mainly driven by minor and major dry mergers, while minor and major wet mergers are relevant in determining the properties of less luminous galaxies. Since the most luminous galaxies have a narrow spread in ages (1.0 × 1010 yr < t < 1.2 × 1010 yr), their metallicities are the main factor that affects their colours. Their mean iron abundances are close to the solar value and have already been reached at z ≈ 1. This fact is consistent with several observational evidence that favour a scenario in which both the slope and scatter of the CMR are in place since z ≈ 1.2. Galaxies in the bright end reach an upper limit in metallicity as a result of the competition of the mass of stars and metals provided by the star formation occurring in the galaxies themselves and by the accretion of merging satellites. Star formation activity in massive galaxies (stellar mass M★ ≳ 1010M⊙) that takes place at low redshifts contributes with stellar components of high metallicity, but the fraction of stellar mass contributed since z ≈ 1 is negligible with respect to the total mass of the galaxy at z= 0. On the other hand, mergers contribute with a larger fraction of stellar mass (≈10-20 per cent), but the metallicity of the accreted satellites is lower by ≈0.2 dex than the mean metallicity of galaxies they merge with. The effect of dry mergers is to increase the mass of galaxies in the bright end, without significantly altering their metallicities. Hence, very luminous galaxies present similar colours that are bluer than those expected if recent star formation activity were higher, thus giving rise to a break in the RS. These results are found for simulated clusters with different virial masses (1014 - 1015h-1M⊙), supporting the idea of the universality of the CMR in agreement with observational results.